Graphdiyne-based sensing interfaces for bioactive molecules: Structural features, structure–activity relationships, and practical challenges - Yingtong Dong; Linbo Li; Junru Li; Jiayao Wulan; Jiale Wei; Daixin Ye; Yuqing Lin (Chemical Engineering Journal, 2026)

Collaborative supply chain management decision-making considering CCUS technology under carbon trading mechanisms - Han Song; Junru Ye; Na Zhou; Jinchai Lin (Environment, Development and Sustainability, 2026)

From SPP to RTK: promoting the satellite navigation potential of acoustically excited antenna - Shangyang Wang; Yifan Fu; Rui Hu; Du Li; Bing Xu; Ruofan Liu; Yinuo Song; Junru Li; Bin Fang; Wenkui Lin; Zhongming Zeng; Xiangwei Zhu (GPS Solutions, 2026)

Chiral CD@Ag2O nanoparticle-mediated highly efficient antibacterial activity based on synergistic multi-pathway interactions - Xiang Li; Qi Ding; Si Li; Junru Li; Heng Zhang; Shan Sun; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2026)

W-induced reconstruction of NiFe (oxy)hydroxides with abundant O-vacancies as efficient electrocatalysts for water oxidation - Zhiqun Bai; Huifang Chen; Weihao Sha; Junru Lin; Jinyuan Miao; Ao Xie; Junqing Pan; Ran Pang; Kai Yan; Pingyu Wan; Yang Tang (Fuel, 2026)

The impact of reactive oxygen species on Fe valence speciation, mineral crystallinity, and nutrient element uptake in rice root iron plaque - Xiaoyu Wang; Junru Huang; Qing Zhang; Yuxi Feng; Yujuan Lin; Meina Liang (Planta, 2026)

Spatial mapping of metabolite distribution in Dendrobium officinale stems across different ages by MALDI-MSI - Junru Huang; Yasmin Khan; Liujuan Cheng; Silin Zhang; Weixiang Xiao; Xu Sun; Lin Liu; Honghong Fan (Food Research International, 2025)

Chirality-enhanced catalytic selectivity of vanadium oxide (V2O4/5) nanoparticles for higher detection sensitivity - Junru Li; Si Li; Shuhan He; Heng Zhang; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2025)

Reversing N-intermediate adsorption configuration over Mo Fe diatomic sites enables enhanced nitrate reduction - Kui Wang; Junru Li; Xinru Wei; Zhiqiang Zhao; Xianbin Meng; Kai Li; Yuzheng Cui; Junjie Mao; Baotao Kang; Yuqing Lin (Chemical Engineering Journal, 2025)

Maternal transcription factor OTX2 directly induces SETD1A and promotes embryonic genome activation in human pre-implantation embryos - Tianlei Zhang; Ziyan Peng; Fei Meng; Zhuo Li; Junru Chen; Qinwei Zhou; Lizhi Leng; Hao Bo; Guangxiu Lu; Yun Deng; Feng Gu; Ge Lin (Science China Life Sciences, 2025)

Comparative transcriptomics of susceptible and resistant Cucumis metuliferus upon Meloidogyne incognita infection - Xiaoxiao Xie; Junru Lu; Runmao Lin; Jian Ling; Zhenchuan Mao; Jianlong Zhao; Qihong Yang; Shijie Zheng; Yan Li; Richard G. F. Visser; Yuling Bai; Bingyan Xie (Planta, 2025)

The Effects of Different Concentrations of Hydrogen-Rich Water on the Growth Performance, Digestive Ability, Antioxidant Capacity, Glucose Metabolism Pathway, mTOR Signaling Pathway, and Gut Microbiota of Largemouth Bass (Micropterus salmoides) - Yin Yuan; Huixiang Li; Songwei Chen; Yongchun Lin; Jiangyuan Peng; Junru Hu; Yongsheng Wang (Fishes, 2024)
Hydrogen-rich water (HRW) is widely recognized for its growth promoting, antioxidant, and anti-inflammatory properties. However, little is known about the role of HRW in aquaculture. This study aims to investigate how different concentrations of HRW affect the growth performance, digestive ability, antioxidant capacity, mTOR signaling pathway, and gut microbiota of juvenile largemouth bass. We randomly assigned 360 fish (13.73 ± 0.1 g) to three treatments. The control group was maintained in regular water, while the treatment groups were treated with different concentrations of H2 dissolved in water, which were H1 (179.65 ± 31.95 ppb) and H2 (280.65 ± 64.43 ppb), respectively. Through an analysis of the three treatments, it was found that H1 significantly increased the final body weight, weight gain rate, specific growth rate, and survival rate, and reduced the feed conversion ratio (p

Impact of dietary zinc on the growth performance, histopathological analysis, antioxidant capability, and inflammatory response of largemouth bass Micropterus salmoides - Hongyan Kou; Xueting Liu; Junru Hu; Gang Lin; Yufan Zhang; Li Lin (Fish & Shellfish Immunology, 2023)

Single-Cell RNA-seq Analysis of a Human Embryonic Stem Cell to Endothelial Cell System Based on Transcription Factor Overexpression - XiangWang Xu; JunRu Chen; Hao Zhao; YuZe Pi; Ge Lin; Liang Hu (Stem Cell Reviews and Reports, 2023)

Anti-inflammatory steroids from the stems of Solanum nigrum L. - Junru Deng; Lin Wang; Qingyu Jin; Jia Zeng; Jingwen Xu; Xiangjiu He; Yihai Wang (Phytochemistry, 2023)

Hydrogen injection reduces ammonia nitrogen and changes microbial community composition in aquaculture water - Shengdi Ning; Junru Hu; Jie Yu; Long Huang; Minjian Lai; Xiangni Li; Yongchun Lin; Wanqing Zhong; Lei Wang (Frontiers in Marine Science, 2023)
The study aimed to investigate the effect of hydrogen on nitrogen and phosphorus removal and microbial community composition in aquaculture water. Two groups were designed separated: Group H was charged with hydrogen and Group D was set as control. Water samples were collected at 0, 1, 2, 3, 4, 5, 6, and 7 days after hydrogen injection to detect not only the content of total nitrogen, ammonia nitrogen and phosphorus, but also microbial community composition in aquaculture water. Our findings have demonstrated that 7-days’ hydrogen treatment could effectively reduce ammonia nitrogen in aquaculture water. And in Day 7, the concentration of ammonia nitrogen in Group D was 1.66 times as that in Group H. Meanwhile, microbial structures in the water bodies of these two groups were significantly different. The abundance of bacteria such as Proteobacteria, Firmicutes, Bacteroidetes, and Desulphuri a increased clearly in Group H, which means nitrification and denitrification occurred in the effect of hydrogen injection. These findings suggested that hydrogen could significantly improve aquaculture water health and reduce the production of ammonia nitrogen, which means hydrogen could be used as a functional external method to protect the aquaculture environment.

Definition of water exchange zone between the Bohai Sea and Yellow Sea and the effect of winter gale on it - Jun Song; Junru Guo; Jing Li; Lin Mu; Yulong Liu; Guosong Wang; Yan Li; Huan Li (Acta Oceanologica Sinica, 2017)

Vertical structure and seasonal variation of tidal and residual currents in the northern Huanghai Sea - Jun Song; Junru Guo; Lulu Qiao; Lin Mu; Zhigang Yao; Yang Liu; Huan Li; Xianwen Bao; Xiaoyan Sun; Jia Gao (Acta Oceanologica Sinica, 2011)